Analisis Rasio Keuangan Pada PT. Bluebird Tbk Setelah Adanya Sarana Transportasi Berbasis Online - Goni, Marchel R. A.; Tampi, Dolina L.; Manoppo, Wilfried S. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study was to analyze the Financial Ratio at PT Bluebird Tbk after the existence of online-based transportation facilities. The company's problem arose since the entry of online transportation facilities where there was a significant decrease in income. Ratio analysis in the opinion of Munawir An analytical method to determine the relationship of certain items in the balance sheet or income statement individually or in a combination of the two reports. The research method used is liquidity ratio, solvability ratio and profitability ratio. The results show that the relationship between liquidity and solability can be said to be "liquid and solvable", meaning that the condition of the company is declared healthy and in good condition because the company is able to pay off its obligations that are due on time. Furthermore, the relationship between solvency and profitability can be said as "solvabel and inprofit", meaning that the condition of total corporate debt tends to decrease, not accompanied by a decrease in profit from year to year. Declining profit growth does not affect the rate of return on short-term debt from the company. This means that even though profits are reduced, the company can still return the current debt fairly well. Thus, after the entry of other online-based transportation facilities there is a downward trend in indicators of profitability, while in the other two indicators tend to be in a good position. This is because the company has not been able to manage financial performance in terms of profitability efficiently.